Pendekatan Ekonomi Terhadap Kerusakan Lingkungan: Peran Willingness To Accept (WTA) Dalam Menilai Dana Kompensasi - Fitri, Yelli (Universitas Bojonegoro, 2025)
Mining activities contribute to air pollution, water contamination, and other environmental disturbances that negatively impact surrounding communities. This study aims to review the Willingness to Accept (WTA) approach in measuring compensation for such environmental damages and to examine the factors influencing the magnitude of WTA values based on previous studies. Using a literature review method, this study analyzes research findings that employ the Contingent Valuation Method (CVM) in the context of mining and environmental pollution. The results indicate that WTA values vary widely depending on regional characteristics, types of pollution, and the socio-economic conditions of the affected communities. Factors such as land area, education level, number of dependents, and distance from the pollution source significantly influence the compensation value. This review highlights that WTA is a relevant approach for formulating fair and evidence-based environmental compensation policies.